A Meta-Analysis of Latinx Acculturation and Intimate Partner Violence. (October 2020) - Alvarez, Miriam J.; Ramirez, Sandra Oviedo; Frietze, Gabriel; Field, Craig; Zárate, Michael A.
Objective: Intimate partner violence (IPV) is a serious public health concern that affects many Latinx couples. The present study conducted a systematic review and meta-analysis to quantitatively assess acculturation as a predictor of IPV among Latinxs and subgroup analyses to evaluate the effect size by gender and type of acculturation measure. Method: The meta-analysis implemented the preferred reporting items for systematic reviews and meta-analyses guidelines to retrieve studies assessing the relationship between acculturation and intimate partner victimization among foreign-born and U.S.-born Latinx adults. A fixed effects model (FEM) and a random effects model (REM) were employed. Additional subgroup analyses examined the strength of the relationship by gender and type of acculturation measure. Results: The meta-analysis included 27 independent effect sizes across 21 studies. An REM yielded a weighted average correlation of .11 (95% confidence interval [.02, .20]). The strength of the correlation differed by scale and ranged from −.003 to .47. For both men and women, higher acculturation was associated with increased IPV. Conclusions: Our results yielded three important findings: (1) the overall effect of acculturation on IPV is relatively small, (2) acculturation differentially influences male-to-female and female-to-male partner violence, and (3) the strength of the correlation between acculturation and IPV differs by scale. This body of work provides evidence for the effect of acculturation on IPV, with potential implications for interventions targeting Latinxs.